PERBEDAAN BERATBIJIDAN PENGARUHNYA TERHADAP DAYA KECAMBAH DAN PERTUMBUHAN KECAMBAH TANAMAN AREN (Arenga pinnata) - Ahmad Masyudi; Armaini Armaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2022)
Sugar palm or palm tree (Arenga pinnata Merr) is a plant that produces industrial materials. Propagation of sugar palm plants can be done generatively using seeds. The problem in seed propagation is that it is not known what the best seed size has the potential to accelerate the process of seed germination and obtain quality seeds. This study aims to determine the effect of sugar palm seed weight and determine the best seed weight for sugar palm plant growth and germination.This research was carried out from April 2021 to August 2021 which was arranged according to a completely randomized design with different sizes of palm seeds consisting of four sizes, namely: < 4.0 g, > 4.0 g – 5.5 g, > 5, 5 g – 7.0 g and > 7.0 g. Parameters observed were germination, seed vigor, germination rate, apokol length, apokol diameter, plumule length and plumule diameter. Data were analyzed using variance and further tested using multiple distance test at 5% level. The results showed that the size of the palm seeds had an effect on seed vigor, apokol length and apokol diameter while seed weight had no effect on germination, germination rate, plumule length and plumule diameter at seed size > 5.5 – 7.0 g indicating germination results and the best germination growth in sugar palm plants. Based on the results of the research that has been carried out, it is expected that when selecting seeds to be used in the germination process and sprout growth using seeds with sizes > 5.5 – 7.0 g.Keywords : palm seeds, seeds weight.